2022
DOI: 10.1039/d2tb02197h
|View full text |Cite
|
Sign up to set email alerts
|

Silica-coated gold nanorods with hydrophobic modification show both enhanced two-photon fluorescence and ultrasound drug release

Abstract: A single functionalization step converted silica-coated gold nanorods into theranostics capable of fluorescence imaging, ultrasound imaging, and drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The loading capacity (mass of DiO per mass of particle) of DiO in DOPC HMSNs was 0.8 ± 0.2%, which was significantly lower than that of DSPC HMSNs: 3.0 ± 0.7% (* p < 0.05). MSNs could not load DiO because of their lack of hydrophobicity, aligning with a past report …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The loading capacity (mass of DiO per mass of particle) of DiO in DOPC HMSNs was 0.8 ± 0.2%, which was significantly lower than that of DSPC HMSNs: 3.0 ± 0.7% (* p < 0.05). MSNs could not load DiO because of their lack of hydrophobicity, aligning with a past report …”
Section: Resultssupporting
confidence: 90%
“…DiO is a green fluorescent, lipophilic dye that can incorporate into lipid matrices . Previous work in our group showed that DiO could be loaded onto DPPC-covered, hydrophobically-modified silica-coated gold nanorods . Here, the encapsulation efficiency (mass of DiO per mass of DiO fed) of DiO in DOPC HMSNs was 4.0 ± 0.8% which was significantly lower than that of DSPC HMSNs: 15.1 ± 3.6% (* p < 0.05) (Figure S10).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Also, studies conducted by Mueller et al demonstrated hydrophobically modified, silica-coated gold nanorods as a versatile theranostic agent. The studies also showed that when contrasted with passive drug release in the absence of ultrasound, ultrasound-mediated circumstances resulted in a 2-fold higher release of nanomedicines . He et al reported a high-performance combination treatment for ablating cancer cells that combined photothermal therapy with chemotherapy to increase therapeutic effectiveness using silica-encapsulated gold nanorods .…”
Section: Functional Materials Platforms In Cancer Theranosticsmentioning
confidence: 99%